The political frontiers of Europe as a civil society: J. Habermas’ rejection of a European Volk and M. Foucault’s balance of power as protections against European nation‐state - Karskens, Machiel (Creativity Studies, 2008)
With the help of J. Habermas and M. Foucault, it is argued that the idea of Europe is, first of all, the ideal of an unlimited civil society. Human rights, the rule of law and the legal European institutions are its political backbone. The European Union itself is somehow the realization of this ideal conception of a borderless, unlimited society. It is argued that the European Union in this respect is a heterotopia within the bordered and sovereign member states themselves. Seen from the outside, however, and in the world of geopolitics, Europe is a political power with closed borders and excluding frontiers. In this respect the European Union is a continuation of the old European Balance of Power. Pozityvios alternatyvos Europos nacijai–valstybei Santrauka. Remiantis J. Habermasu ir M. Foucault, Europos idėja straipsnyje traktuojama kaip neribotos pilietinės visuomenės idealas, kurio politinį pagrindą sudaro žmogaus teisės, įstatymo valdžia ir teisinės Europos institucijos. Tam tikra prasme šią idealią sienų neturinčios, neribotos visuomenės koncepciją realizuoja pati Europos Sąjunga. Šia prasme, žvelgiant iš „vidinės“ suverenių, turinčių sienas narių valstybių perspektyvos, ji laikytina heterotopija. Tačiau, žvelgiant iš išorės ir geopolitiškai, Europa yra politinė galia su uždaromis sienomis, griežtai sauganti savo ribas. Šiuo atžvilgiu Europos Sąjunga gali būti vertinama kaip senojo europietiškojo galios pusiausvyros projekto tąsa. Reikšminiai žodžiai: galios pusiausvyra, pilietinė visuomenė, Europa, Europos Sąjunga, heterotopija. First Published Online: 14 Oct 2010